Return to the 20th century: seventy years of psychiatry, psychoanalysis and psychosomatic medicine in Santiago, Chile - Florenzano U., Ramón (Revista de Psiquiatría Clínica, 2021)
This paper summarizes the changes in clinical psychiary, psychoanalysis and psychosomatic medicine in the last century. It takes as examples two chilean physicians, an internist and a psychiatrist that influenced the author. Drs. Hernán Alessandri Rodríguez and Ignacio Matte Blanco trained physicians not only in the Facultad de Medicina of the Universidad de Chile, but in a nationaland global level, leaving a seal that lasts until the present. The article reviews the history of that Facultad, as well as the one of the Clínica Psiquiátrica Universitaria that was directed by Professor Matte. He was also the founder of the Asociación Psicoanalítica Chilena, accepted as a component society in August 1949 of the International Psychoanalytic Association. Historical antecedents of freudian psychoanalysis and psychosomatic medicine are reviewed until half 20th century. The posterior advances of clinical psychiatry, post freudian psychoanalysis and chilean mental health are described. The conclusión is reached that the personalities, family backgrounds and socio-cultural context are all related to the improvements and difficulties in health problems